2016
DOI: 10.1002/jcp.25429
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Diabetic Agent Sodium Tungstate Induces the Secretion of Pro‐ and Anti‐Inflammatory Cytokines by Human Kidney Cells

Abstract: Diabetic kidney disease (DKD) is the major cause of end stage renal disease. Sodium tungstate (NaW) exerts anti-diabetic and immunomodulatory activities in diabetic animal models. Here, we used primary cultures of renal proximal tubule epithelial cells derived from type-2-diabetic (D-RPTEC) and non-diabetic (N-RPTEC) subjects as in vitro models to study the effects of NaW on cytokine secretion, as these factors participate in intercellular regulation of inflammation, cell growth and death, differentiation, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition to angiogenesis, microinflammation plays an important role in the development and progression of DKD [34][35][36][37][38]. Both intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) have been found to be upregulated in DKD; as suggested by their names, these two factors facilitate the adhesion of inflammatory cells and recruit circulating immune cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to angiogenesis, microinflammation plays an important role in the development and progression of DKD [34][35][36][37][38]. Both intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) have been found to be upregulated in DKD; as suggested by their names, these two factors facilitate the adhesion of inflammatory cells and recruit circulating immune cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we observed that PEPCK immunostaining was severely reduced only in those cortical proximal tubules affected by glycogenic alteration in NaW-IRS2-KO mice. It has been reported that NaW, as an insulin-mimetic agent, downregulates PEPCK expression in the liver from WT diabetic rats [ 22 ] and in human proximal tubules in vitro [ 23 ]. However, previous findings described an inconsistent effect of NaW in downregulating PEPCK in the liver from IRS2-KO mice [ 4 ], suggesting that IRS2 expression is required.…”
Section: Discussionmentioning
confidence: 99%
“…(e) Na 2 WO 4 induces DNA damage (Guilbert et al, ; Kelly et al, ) and cell cycle arrest (Bertinat, Silva, et al, ; Guilbert et al, ; Liu et al, ; Osterburg et al, ), precluding cell senescence and the secretion of senescence‐associated products that can fuel cell transformation by targeting the tumor microenvironment (Sturmlechner et al, ). (f) Na 2 WO 4 stimulates cytokine secretion, among these the angiogenic factor VEGF‐A (Bertinat, Silva, et al, 2015) and the proinflammatory factors IL‐6, IL‐8, and MCP‐1 (Bertinat et al, ), which are critical players in tumor development and progression, acting in an autocrine and paracrine fashion. The Janus kinase (JAK)–signal transducer and activator of transcription (STAT)‐3 and ERK1/2 pathways are the major cascades activated by IL‐6 and IL‐8, but are also activated by different growth factors and show cross talk with many other signaling pathways (McGuire & Fitzpatrick, ; Taniguchi & Karin, ).…”
Section: Na2wo4 and Renal Carcinogenesis: Hypothesismentioning
confidence: 99%
“…(e) Na 2 WO 4 induces DNA damage (Guilbert et al, 2011;Kelly et al, 2013) and cell cycle arrest (Bertinat, Silva, et al, 2015;Guilbert et al, 2011;Liu et al, 2012;Osterburg et al, 2010), precluding cell senescence and the secretion of senescence-associated products that can fuel cell transformation by targeting the tumor microenvironment (Sturmlechner et al, 2017). (f) Na 2 WO 4 stimulates cytokine secretion, among these the angiogenic factor VEGF-A (Bertinat, Silva, et al, 2015) and the proinflammatory factors IL-6, IL-8, and MCP-1 (Bertinat et al, 2017), which are critical players in tumor development and progression, acting in an autocrine and paracrine fashion.…”
Section: Na 2 Wo 4 and Renal Carcinogenesis: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation